The Relationship Between Self-Efficacy And Assertiveness On Student Career Decision Making At SMK Negeri 1 Gunung Sahilan - Assahrawiza; Firman; Netrawati; Mohd Nazri Abdul Rahman (Quality : Journal Of Education, Arabic And Islamic Studies, 2024)
The purpose of this study is to investigate the links that exist between the following three aspects: Students at SMKN 1 Gunung Sahilan were asked to answer three questions: 1) The correlation between self-efficacy and assertiveness in relation to career decision making; 2) The relationship between self-efficacy and career decision making at SMKN 1 Gunung Sahilan students; and 3) The relationship between assertiveness and career decision making among students at SMKN 1 Gunung Sahilan. For the purpose of this study, a quantitative methodology and an associative research design were utilized. A total of 101 students were chosen for this study using a selection technique known as proportionate random sampling. The total number of students who participated in this study was 404. A questionnaire based on the Likert scale is used as the method of data collection. This questionnaire is designed to precisely target students' self-efficacy, assertiveness, and decision making. The evaluation of the data in this study is carried out with the assistance of SPSS Version 16.0 for Windows when employing multiple regression analysis techniques.